Optimal remanufacturing strategies for original equipment manufacturers: partner and mode selection - Zhou, Qin (2023)
This study examines a supply chain with three players which are a contract manufacturer (CM), an independent remanufacturer (IR) and an original equipment manufacturer (OEM). The OEM outsources the production process of new products to the CM and enters the remanufacturing market by cooperating with the remanufacturer which can either be the CM or IR through outsourcing or authorization remanufacturing modes. We investigate the OEM's remanufacturing partner choice when the remanufacturing mode is given, and the remanufacturing mode choice when the remanufacturer is selected. We consider profitability and environmental performance as the OEM's decision-making criteria. When the wholesale price of the new product is exogenously determined, we find that cooperating with the remanufacturer that has a lower variable cost is the dominant strategy given a specific remanufacturing mode. When the CM strategically determines the wholesale price of the new product, the OEM should never select the CM as the remanufacturing partner, and the IR is always a preferable remanufacturing partner for the OEM. In addition, both outsourcing and authorization modes are optimal when the CM is the remanufacturer. However, when the IR is the remanufacturer, the OEM should always choose the outsourcing mode.